Sharp Bounds on the Spectral Radii of Uniform Hypergraphs concerning Diameter or Clique Number - Qiannan Niu; Haizhen Ren; Lei Zhang (Discrete Dynamics in Nature and Society, 2021)
In this paper, we defined two classes of hypergraphs, hyperbugs and kite hypergraphs. We show that balanced hyperbugs maximize the spectral radii of hypergraphs with fixed number of vertices and diameter and kite hypergraphs minimize the spectral radii of hypergraphs with fixed number of vertices and clique number.